The Influence of E-Service Quality and Brand Ambassadors in Forming Consumer Confidence that has an Impact on Consumer Buying Interest in the Tokopedia Application - Ade Syilvianita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the direct influence of the influence of e-service quality and brand ambassadors in shaping consumer trust which has an impact on consumer buying interest in the Tokopedia application. The sampling technique used was purposive sampling method. The analytical method used in this study is the Structural Equation Model- Partial Least Square (SEM-PLS) on SmartPLS 3.0 software to test the strength of direct and indirect relationships between variables. The results of this study indicate that there is a significant direct effect between E-Service Quality and Consumer Trust. There is a significant direct influence between Brand Ambassador and Consumer Trust. There is a significant direct effect between E-Service Quality and Purchase Interest. There is an insignificant direct influence between Brand Ambassador and Buying Interest. There is a significant direct effect between Consumer Confidence and Purchase Intention. In this study, the influence of e-service quality and brand ambassadors in shaping consumer trust that has an impact on consumer buying interest in the Tokopedia application has a direct and indirect influence. In this study, there is a mediating role, namely consumer trust. The independent variables are E-Service Quality and Brand Ambassador. While the intervening variable in this study is Consumer Trust and the dependent variable in this study is Purchase Interest